Great Christian jurists in Spanish history / edited by Rafael Domingo and Javier Martínez-Torrón. - Domingo, Rafael, 1963-; Martínez-Torrón, Javier (Law and Christianity., 2018)
The Great Christian Jurists series comprises a library of national volumes of detailed biographies of leading jurists, judges and practitioners, assessing the impact of their Christian faith on the professional output of the individuals studied. Spanish legal culture, developed during the Spanish Golden Age, has had a significant influence on the legal norms and institutions that emerged in Europe and in Latin America. This volume examines the lives of twenty key personalities in Spanish legal history, in particular how their Christian faith was a factor in molding the evolution of law. Each chapter discusses a jurist within his or her intellectual and political context. All chapters have been written by distinguished legal scholars from Spain and around the world. This diversity of international and methodological perspectives gives the volume its unique character; it will appeal to scholars, lawyers, and students interested in the interplay between religion and law.